The role of nurse leaders in bridging research and clinical practice - Akbar, M Agung (Indonesian Journal of Health Services, 2025)
Postoperative pain following cesarean section is a common clinical problem that may affect Nurse leaders play a strategic role in bridging the gap between research findings and clinical practice in healthcare services. The integration of research evidence into evidence-based nursing practice is essential for improving healthcare quality and patient safety. This editorial article aims to discuss the critical role of nurse leaders in facilitating the implementation of evidence-based practice within clinical settings. The discussion highlights the leadership function of nurse leaders as connectors between researchers and practitioners, translators of research findings into practical clinical guidelines, and drivers of organizational change in healthcare institutions. Nurse leaders also contribute to fostering collaborative cultures between academia and clinical practice, ensuring the availability of resources to support research implementation, and developing policies that promote evidence-informed clinical decision-making. In addition, nurse leaders serve as role models in the adoption of evidence-based practice and encourage nurses to engage in research and quality improvement initiatives. Strong nursing leadership can therefore enhance the effective integration of research and clinical practice, ultimately improving healthcare quality and advancing the nursing profession.